2019
DOI: 10.1002/jor.24334
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Interleukin 17A/F Locus Haplotypes Are Associated With Increased Risk to Hip and Knee Osteoarthritis

Abstract: We studied the genetic epidemiology of primary large-joint (hip and knee) osteoarthritis (OA), in order to find disease risk factors by a candidate-gene approach. We used case-control study in the Croatian Caucasian population. We genotyped 500 OA patients (260 hip, 240 knee; both with total joint replacements) and 597 healthy individuals for single-nucleotide polymorphisms (SNPs) in interleukin 17A (IL17A) (rs2275913) and IL17F (rs763780 and rs1889570) genes. On the basis of our population and allelic and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…1). Finally, we identified six case-control studies about the association between [19], only allele model was analyzed in the overall population and Caucasian population. More characteristics of the included articles are shown in Tables 1 and 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Finally, we identified six case-control studies about the association between [19], only allele model was analyzed in the overall population and Caucasian population. More characteristics of the included articles are shown in Tables 1 and 2.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Jiang [14] and Han [15] found that the IL-17A(rs2275913) polymorphism was involved in high risk of KOA while the IL-17F(rs763780) was not. Bai [16] and Eftedal [19] found that IL-17A/F gene polymorphisms all related to the high-risk knee OA occurrence. Bafrani [18] found that IL-17A(rs2275913) gene may be a protective factor against knee osteoarthritis while the IL-17F(rs763780) gene may be a risk factor for knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a genetic epidemiology study of HOA found that the IL17A-IL17F haplotype (rs2275913-rs763780-rs1889570) G-C-A confers predisposition to HOA, and the IL17A-IL17F haplotype (rs2275913-rs763780) G-T is associated with protection from HOA in a Croatian population. 11 These results can explain a small portion of the heritability, but to date, the molecular mechanisms of HOA remain largely unknown. Furthermore, to the best of our knowledge, although 4 case-control studies have reported the relationship between the IL17F gene and knee OA with conflicting results in a Han Chinese population, there has been no study of the association of the IL17F gene with HOA in a Han Chinese population.…”
mentioning
confidence: 99%
“…While problems with abrasive wear of implanted hip arthroplasty materials and treatment of infections have been adequately addressed, the etiology of the non‐mechanical non‐infectious aseptic loosening of hip endoprostheses has not been established yet . The time period from implantation to aseptic loosening varies significantly between different patients with identical implants, and recent studies in this field have focused attention to possible differences in genetic host factors and polymorphisms with variability in the immune response to exogenous materials and a different response of individuals’ host tissues to external mechanical stimuli …”
mentioning
confidence: 99%